Estudio definitivo del sub sector hidráulico del canal Garcia, distrito de Mochumi, provincia de Lambayeque, departamento de Lambayeque - Coronel Salazar, Frank Carlos (2022)
The present thesis project called "Definitive Study of the Water Sub-Sector of the Garcia Canal, district of Mochumí, province of Lambayeque, department of Lambayeque", is about a second-order irrigation canal that belongs to the Mochumí irrigation subsector. This canal has a length of 7,213.25 km, with an average slope of 1.08% or, with an initial flow of 1.00 m3 / s that provides irrigation water to 450.81 ha (With License and Permit). The main problem of the García canal is the loss of water due to infiltration and the poor condition of the hydraulic infrastructure, which causes losses of up to 12% of the current water. Due to these problems, this thesis project aims to develop all the engineering studies necessary to carry out the lining of the García canal in order to improve the quality of the conduction and distribution of water for irrigation. The hydrological and meteorological information was provided by the National Service of Meteorology and Hydrology (SENAMHI) of Peru, where data from the Lambayeque station was used, which has been selected for its proximity to the study are